2020
DOI: 10.1002/ces2.10036
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural effects on hardness and optical transparency of birefringent aluminosilicate nanoceramics

Abstract: Transparent nanoceramics, synthesized at extreme conditions of high pressure and temperature, are new classes of materials highly attractive for photonic applications, such as optical windows, which require additional increased hardness and toughness. In this study, mechanical properties of transparent polycrystalline nanoceramics consisting of triclinic Al2SiO5 kyanite (~91.4 vol%) and trigonal Al2O3 corundum (~8.6 vol%) fabricated at high pressure (10 GPa) and temperature (1200‐1400°C) were investigated. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Additional details can be found elsewhere. 17,22 The high-pressure synchrotron in situ X-ray and ultrasonic measurements were implemented with the 1500-ton multianvil large volume press SPEED1500 located at SPring-8 (beamline BL04B1). 19 For this, the carefully diamond-mediated polished NPK (~0.8 µm mirror-surface; sample size of ~2.2 mm in diameter and ~0.7 mm in height) was fit into a MgO sleeve and both covered by (Mg, Co)O pressure medium (1)…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional details can be found elsewhere. 17,22 The high-pressure synchrotron in situ X-ray and ultrasonic measurements were implemented with the 1500-ton multianvil large volume press SPEED1500 located at SPring-8 (beamline BL04B1). 19 For this, the carefully diamond-mediated polished NPK (~0.8 µm mirror-surface; sample size of ~2.2 mm in diameter and ~0.7 mm in height) was fit into a MgO sleeve and both covered by (Mg, Co)O pressure medium (1)…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It has been previously shown that the hardness of the NPK is positively affected by the Hall-Petch behavior. 17 It is tempting to apply Equation (13) to the NPK, but it may be speculative because it is explicitly for non-nanocrystalline materials. However, the calculated hardness value (H V,calc = 18.2(4) GPa) of the NPK by Equation (13) using our obtained bulk and shear modulus is consistent to the corresponding experimentally measured one (H V,exp = 18.3(11) GPa).…”
Section: F I G U R Ementioning
confidence: 99%
See 3 more Smart Citations